Nitrogen balance and leucine kinetic approaches to the examination of protein requirements and protein metabolism in resistance athletes - Tarnopolsky, Mark A. (My University, 1991)
Previous work has demonstrated that resistance exercise may increase dietary protein (PRO) requirements to a varying degree. Much of these discrepancies probably arose from differences in training intensity, classification of exercise, habituation to a training stimulus, and methodological considerations such as: 1. inadequate dietary adaptation periods; 2. failure to measure routes of nitrogen (N) loss (i.e., sweat); 3. failure to measure the dietary PRO (nitrogen (N)) content; 4. collection periods too short to measure an impact of exercise (i.e., delay in N excretion due to dehydration); and 5. the use of measurements insensitive to short-term alterations in PRO metabolism (i.e., lean body mass estimate from skinfolds to assess changes in muscle mass over a week of treatment). In addition, there is a paucity of information quantitating the influence of acute and chronic resistance exercise on PRO turnover. The overall purpose of this thesis was to examine N metabolism and the PRO requirements of resistance athletes, under well controlled conditions, with three discrete, but related studies. The first investigation was a randomized, cross-over study designed to determine the dietary PRO requirements of young men performing intensive body building resistance exercise during the early stages of training (novice) and to determine whether the consumption of excessive amounts of PRO had an ergogenic (work enhancing) effect upon muscle mass/strength gains. Twelve inexperienced, young, male volunteers received either a PRO supplement (total PROIN=2.62 g·kg⁻¹·d⁻¹) or a carbohydrate (CHO) supplement (total PROIN=1.35 g·kg⁻¹·d⁻¹) each for a period of 4 weeks during intensive (1.5 h·d⁻¹, 6 d·wk⁻¹) circuit weight training. Nitrogen balance (NBAL) measurements taken over the last 3 days on each diet were used to determine that the PRO intake (PROIN) for zero NBAL was 1.43 g·kg⁻¹·d⁻¹ (+1SD=1.62 g·kg⁻¹·d⁻¹ (recommended intake)). Pre- and post-training measurements of strength and estimates of muscle mass (density, creatinine excretion, and biceps muscle N content) were not different between diet treatments in spite of a significant training effect (increased strength and lean body mass) due to the exercise programme. It was recommended that young males performing body building-type resistance exercise require a dietary PROIN of 1.62 g·kg⁻¹·d⁻¹ during the first 2 months of training and that there are no greater increases in strength or muscle mass by consuming PRO in excess of this amount. The acute effects of resistance exercise upon leucine oxidation and whole body PRO synthesis (WBPS) were studied using stable isotope methodology in the second study. L-[1-¹³C] leucine was used as a tracer to calculate these variables in 6 healthy, fed, male athletes in response to a 1 h bout of circuit-set resistance exercise. The measurements were performed prior to, during and for 2 h after exercise and corrections were made for the background ¹³CO₂/¹²CO₂ breath enrichment and bicarbonate retention factor (c). Results demonstrated significant increases in the background ¹³CO₂/¹²CO₂ breath enrichment at 1 and 2 h after exercise and in c during exercise. At 15 min after exercise c was significantly lower than at rest. There were no effects of exercise on leucine oxidation, WBPS, nor the rate of appearance of endogenous leucine or total leucine flux. We concluded that circuit-set resistance exercise did not affect the measured variables of leucine metabolism. In addition, large errors in calculating leucine oxidation and WBPS during resistance exercise can occur if background ¹³CO₂/¹²CO₂ breath enrichment and c are not accounted for. In the final study, leucine kinetics and NBAL were used to determine the dietary PRO requirements of sedentary (S) and resistance trained (BB) subjects. Each subject was randomly assigned to each of 3 dietary PROIN (LP=0.86; MP=1.40; HP=2.40 g PRO·kg⁻¹·d⁻¹) for a total period of 13 days. Over the last 3 d, NBAL measurements were completed and on the last day WBPS and leucine oxidation were determined from L-[1-¹³C] leucine turnover. Regression analysis of the NBAL data was used to determine the PROIN for zero NBAL for S=0.69 g·kg⁻¹·d⁻¹ and BB=1.41 g·kg⁻¹·d⁻¹ and a recommended intake (ZERO intake +1 SD) for S=0.89 g·kg⁻¹·d⁻¹ and BB=1.76 g·kg⁻¹·d⁻¹. For BB the LP diet did not provide adequate PRO and resulted in an accommodated state (↓ WBPS vs MP and HP), the MP diet resulted in a state of adaptation as evident by the increase in WBPS (vs LP) and no increase in leucine oxidation (vs LP), while the HP diet did not result in increased WBPS compared to the MP diet but leucine oxidation did increase significantly indicating a nutrient overload. For S the LP diet provided adequate PRO and increasing PROIN did not increase WBPS. Leucine oxidation increased for S on HP diet. Taken together, these results indicated that the MP and HP diets were nutrient overloads for S. There were no effects of dietary treatment on indices of lean body mass (creatinine excretion, body density) for either group. Overall, this research provided evidence that the PRO requirements of resistance athletes are greater than for sedentary individuals and are above current Canadian and U.S. recommended daily PROIN for young, healthy males. The second study demonstrated that acute resistance exercise did not affect whole body leucine turnover and, in contrast to endurance exercise, there was no significant increase in leucine oxidation during exercise. In addition, this study demonstrated that changes occur in c and background breath enrichment during and after resistance exercise that can have an impact on leucine oxidation measurements. The final study also demonstrated that the positive NBAL that occurs at high PROIN does not appear to represent a physiological entity (i.e., no increase in WBPS or lean mass) but is probably an error in the NBAL method.
Keywords: Medical Sciences; Medical Sciences